Bark Content of a Mature Eucalypts Tree - Rawat, J. K. (Indian Forester, 1989)
Bark volume table for the whole tree and for the timber produced by tbe tree have been presented for mature (8 to 10 years old) Eucalyptus hybrid in North Haryana. Bark is found to constitute nearly one-fifth of the overbark volume of a tree. If only the timber portion of the tree is considered, tbe bark content for trees of over 100 cm girth is more than 23 per cent.